A fatal case of adenovirus encephalitis in an adult with end-stage renal disease - Cheong, Xiong Khee; Tan, Juen Kim; Zainulabid, Ummu Afeera; Kori, Najma; Periyasamy, Petrick Ramesh (Springer Nature, 2025)
The spectrum of adenovirus infection can vary from self-limiting mild respiratory illness or gastroenteritis to fatal disseminated disease in immunocompetent hosts. Severe disseminated disease is commonly seen in immunocompromised hosts, including severe pneumonia with acute respiratory distress syndrome, hepatitis, encephalitis, hemorrhagic cystitis, and shock. Meningoencephalitis is a rare manifestation in immunocompetent adults. Early detection of adenovirus infection is necessary as early initiation of appropriate antiviral therapy may prevent life-threatening complications. In this report, we describe a fatal case of adenovirus encephalitis in an adult with end-stage renal disease (ESRD) who presented with a first-onset seizure. The seizure was preceded by a prodromal respiratory illness and septicemic shock, and the diagnosis was confirmed by cerebrospinal fluid (CSF) polymerase chain reaction (PCR) positivity for adenovirus and characteristic electroencephalography (EEG) findings.